(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Actinomycetes are virtually unlimited sources of novel compounds with many therapeutic applications and hold a prominent position due to their diversity and proven ability to produce novel bioactive compounds. The present study “Marine actinomycetes: a new source of compounds against uropathogens” is aimed to prove the antagonistic activity of marine actinomycetes against uropathogens. 13 marine actinomycetes were isolated from various marine sediment samples collected from different stations of Menamkulam coastal region, part of Arabian Sea on the western coast of India. The sample collection and isolation of actinomycetes were done by following the standard microbiological methods and the isolated colonies were characterized based on their morphological parameters.. The morphologically distinct 10 isolates obtained in the present study, the isolates SD96,SD97,SD98,SD99,SD100,SD101,SD102,V107,V108,V109,V110 and V111, among them three isolates, SD99,SD100 and SD102 showed significant antagonism against selected uropathogens collected from a tertiary care center in Kerala. The results were promising and indicated that actinomycetes with distinctive biological activity are abundant in the marine environment along Kerala’s coast.